2014
DOI: 10.1002/jbm.a.35234
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of adhesion and promotion of osteogenic differentiation of human adipose stem cells by poled electroactive poly(vinylidene fluoride)

Abstract: Poly(vinylidene fluoride) (PVDF) is a biocompatible material with excellent electroactive properties. Nonelectroactive α-PVDF and electroactive β-PVDF were used to investigate the substrate polarization and polarity influence on the focal adhesion (FA) size and number as well as on human adipose stem cells (hASCs) differentiation. hASCs were cultured on different PVDF surfaces adsorbed with fibronectin and FA size and number, total adhesion area, cell size, cell aspect ratio and FA density were estimated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 50 publications
(142 reference statements)
6
80
0
1
Order By: Relevance
“…Contrary to the effects observed for muscle cells, higher adhesion and proliferation of MC3T3‐E1 preosteoblast was observed in “poled +” β‐PVDF samples . However, with human adipose stem cells, “poled −” β‐PVDF exhibited significantly larger total focal adhesion than nonpoled and “poled +” samples, and consequently an improved cell differentiation . These results indicate, as mentioned above, that cell adhesion is improved by the charged surfaces.…”
Section: Influence Of Pvdf Microstructures On Cell Morphologymentioning
confidence: 63%
“…Contrary to the effects observed for muscle cells, higher adhesion and proliferation of MC3T3‐E1 preosteoblast was observed in “poled +” β‐PVDF samples . However, with human adipose stem cells, “poled −” β‐PVDF exhibited significantly larger total focal adhesion than nonpoled and “poled +” samples, and consequently an improved cell differentiation . These results indicate, as mentioned above, that cell adhesion is improved by the charged surfaces.…”
Section: Influence Of Pvdf Microstructures On Cell Morphologymentioning
confidence: 63%
“…In fact, studies conducted in cell culture have indicated some advantageous aspect of PVDF polymer for animal implants. These results indicated high proliferation of the osteoblast cells, which are bone cells, in PVDF films [28], and more bioactivity in the polar PVDF phase (β-PVDF) and poled PVDF films, mainly under mechanical stimuli [29,30]. Currently, a novel generation of highly advanced PVDF-based implants has been thought and developed, as those where PVDF-based nanogenerators, that were successfully implanted/tested in rats [31], attested the applicability of PVDF for bio-applications.…”
Section: (Propriedades Mecânicas E Bioativas Do Compósito Pvdf-bcp) Rmentioning
confidence: 87%
“…In this way, considering previous reports where the influence of the electric charge surface on the activity of biomaterials [25] was pointed out and discussed, it is ease to intuit that piezoelectric materials can be used to catalyze biological responses. Recent studies have been conducted in order to understand the potentialities of the polyvinylidene fluoride [(C 2 H 2 F 2 ) n or PVDF] matrix composites in human implants [26][27][28][29][30][31][32]. In this way, different biological applications have been thought for PVDF polymer, leading to different synthesis technique and sample architectures, as scaffold, for example [27].…”
Section: (Propriedades Mecânicas E Bioativas Do Compósito Pvdf-bcp) Rmentioning
confidence: 99%
“…Piezoelectric polymers can be used as a bioactive electromechanically responsive materials for improving tissue engineering strategies [3]. Studies reveal that electrical stimulation influences cell proliferation, differentiation and regeneration [2] both under static [4,5] and dynamic conditions [6]. These results show the potential of such materials for the development of a new generation of wireless electrically active scaffolds and structures for biomedical applications [2].…”
Section: Introductionmentioning
confidence: 93%